The growth and development of Chlorella Vulgaris in the batch culture system. Issue 1 (1st February 2023) - Zaini, N; Kasmuri, N
Abstract: Phytoremediation technique using microalgae has been critically explored nowadays. This method has been employed to achieve cleaner production for a sustainable future. Moreover, phytoremediation imprints green technology as a promising alternative in long–term best management practices. Here, the research aims to cultivate the microalgae, in this case, Chlorella Vulgaris, in the batch culture system using three different mediums (wastewater effluent from wastewater treatment plant UiTM Dengkil, synthetic wastewater and nitrification medium). Optimum conditions such as an aeration system and an ambient environment with sufficient sunlight have been provided for microalgae growth. Here, the performance of Chlorella Vulgaris on the uptake of ammonia-nitrogen, nitrite-nitrogen, nitrate-nitrogen, and phosphorus for the three mediums was observed daily until 14 days. From the results obtained, synthetic wastewater has been considered the suitable medium for the uptake of Chlorella Vulgaris . It can be observed that the percentage removal for nitrate-nitrogen, nitrite-nitrogen, ammonia-nitrogen, and phosphorus were 54.84%, 80.38%, 91.03%, and 67.21%, respectively. There is also a substantial increase in Chlorella Vulgaris growth in 14 days of cultivation in the synthetic wastewater medium. Moreover, it can be expected that the days of observation can be extended to achieve higher growth of Chlorella Vulgaris . Thus, it can portray a clearer insight into the performance of the microalgae for the degradation of the pollutants concerns.